Possible Role of PHD Inhibitors as Hypoxia-Mimicking Agents in the Maintenance of Neural Stem Cells’ Self-Renewal Properties - Wu, Li-Ying; He, Yun-Ling; Zhu, Ling-Ling (Frontiers in Cell and Developmental Biology, 2018)
Hypoxia is the most critical factor for maintaining stemness. During embryonic development, neural stem cells (NSCs) reside in hypoxic niches, and different levels of oxygen pressure and time of hypoxia exposure play important roles in the development of NSCs. Such hypoxic niches exist in adult brain tissue, where the neural precursors originate. Hypoxia-inducible factors (HIFs) are key transcription heterodimers consisting of regulatory α-subunits (HIF-1α, HIF-2α, HIF-3α) and a constitutive β-subunit (HIF-β). Regulation of downstream targets determines the fate of NSCs. In turn, the stability of HIFs-α is regulated by prolyl hydroxylases (PHDs), whose activity is principally modulated by PHD substrates like oxygen (O2), α-ketoglutarate (α-KG), and the co-factors ascorbate (ASC) and ferrous iron (Fe2+). It follows that the transcriptional activity of HIFs is actually determined by the contents of O2, α-KG, ASC, and Fe2+. In normoxia, HIFs-α are rapidly degraded via the ubiquitin-proteasome pathway, in which PHDs, activated by O2, lead to hydroxylation of HIFs-α at residues 402 and 564, followed by recognition by the tumor suppressor protein von Hippel–Lindau (pVHL) as an E3 ligase and ubiquitin labeling. Conversely, in hypoxia, the activity of PHDs is inhibited by low O2 levels and HIFs-α can thus be stabilized. Hence, suppression of PHD activity in normoxic conditions, mimicking the effect of hypoxia, might be beneficial for preserving the stemness of NSCs, and it is clinically relevant as a therapeutic approach for enhancing the number of NSCs in vitro and for cerebral ischemia injury in vivo. This study will review the putative role of PHD inhibitors on the self-renewal of NSCs.